ANTIBIOTICS USE AND AWARENESS OF RISKS ASSOCIATED WITH ANTIMICROBIAL RESISTANCE AMONG FISH FARMERS IN KATSINA STATE, NIGERIA - Akeem Babatunde Dauda; Abdulsalam Sani Nababa; Justina Omolegho Oshoke; Hauwau Abubakar Salele; Ismail Ayoade Odetokun; Ibraheem Ghali-Mohammed; Oluwasesan M. Bello; Awawu Dasuki (Tropical and Subtropical Agroecosystems)
Background. Disease outbreaks are considered to be a significant drawback in aquaculture development globally which leads aquaculturists to indiscriminate use of antibiotics. Objective. To assess the status of antibiotics use, farmers’ knowledge of risks associated with antimicrobial resistance (AMR), and disease occurrence in fish farms in Katsina state, Nigeria. Methodology Semi-structured questionnaires were  administered to the active and accessible fish farms in the state, The data collected were presented and analyzed using descriptive statistics and binary logistic regression. Results: Most of the respondents were male (87.5%), aged 31 to 40 years and average of 7 years in operation. The majority (78.1%) use antibiotics for curative purposes, and the dominant usage frequency was occasional (28.1%). Majority (75%) of the respondents noted that antibiotics are readily available and moderately priced (46.9%) while the method of addition to water (37.5%) was the most frequently. Fish cure™ (37%), Aquaceryl plus™ (26%) and Oxytetracycline (10%) were the most commonly used antibiotics in the state. Most of the respondents (65.6%) are aware of the risks associated with AMR for fish but many of them (56.2%) are not aware of possible risks associated with consuming fish with antibiotic residue. Disease occurrence is very high (78.1%) among the farms in the state, with the majority (59.3%) having experienced outbreaks between one and three times.  Despite the small scale of fish farming in the state, the mean economic loss due to disease outbreaks stood at ₦594, 605.3±0.21 (USD 371.63). The logistic regression model revealed that years in operation is the major factor influencing the use of antibiotics (P=0.072) and the occurrence of fish diseases (P=0.055) in fish farms in the state. Implication: Antibiotics is highly used in fish farms in the state without prescription by the veterinary experts and the majority of the farmers are not aware of risk associated with consuming fish with antibiotic residue. Conclusion.The study collectively provide a foundation for informed decision-making, targeted interventions, and future research directions in the realm of sustainable and responsible aquaculture practices in Katsina state.